TINJAUAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 SEBAGAI KONSTITUSI YANG ISLAMI - Hudiana, Raihan (UI Scholars Hub, 2020)
The Constitution as a form of collective agreement is an important document containing values to be the highest referral system in regulating the life of nation and state. Looking at the sociological fact that Muslims are the majority in Indonesia, the spirit that was built at the beginning was to ensure the absolute necessity of how the basic values and main concepts of Islam can be fulfilled, while keeping in mind the needs and ensuring the rights of people from other religions. The view of some Muslims who assume founding father Indonesia has injured the spirit of the struggle of Muslims in achieving independence and make Indonesia as a secular state would be important to be straightened out. Departing from that, the author will examine the literature how the history and content of the 1945 Constitution in which contains Islamic values. The results of this study indicate that although Indonesia is not an Islamic country, but the spirit and values contained in the 1945 Constitution is very thick breath Islamic values.